Race and the Income-Achievement Gap - Ryan Bacic; Angela Zheng (Institute of Labor Economics (IZA), 2023)
A large literature documents a positive correlation between parental income and child test scores. In this paper, we study whether this relationship, the dependence of the cognitive skills of children on the socioeconomic resources of their parents, varies across race. Using education data linked to tax records, we find that the income-achievement gap is small for East Asian children while significantly larger for Indigenous children. School-level factors explains a large portion of the variation in the gap across race. Our results suggest that the large income-achievement gap for Indigenous students may be rooted in inequality in special needs status.
Keywords: I20; I24; J15; 330; test scores; income-achievement gaps; race